Peran Guru Bk Terhadap Pendidikan Karakter Siswa Kelas IX Di SMPN 2 Depok Kab. Cirebon - Raminah, Inah; Nurdianah, Fitriyah (Bimbingan dan Konseling, FKIP, Universitas Nahdlatul Ulama Cirebon, 2023)
This study aims to determine: 1) Describe the role of BK teachers at SMPN 2 Depok. 2) Describe the character education of students at SMPN 2 Depok. 3) Describe the role of BK teachers in character education of students at SMPN 2 Depok, Cirebon Regency. The method used in quantitative descriptive research. The population in this study were all grade IX students of SMPN 2 Depok totaling 187 students. The researcher used cluster random sampling. The sample in this study were grade IX students who were taken randomly with a total of 32 students. The instruments and data collection techniques used questionnaires and documentation. From the results of the descriptive analysis that has been carried out, it can be concluded that the role of BK teachers at SMPN 2 Depok is included in the good category, this is evidenced by the results of the questionnaire on the role of teachers who were present. by BK teachers with a frequency of (73.91%). This means that the role of BK teachers at SMPN 2 Depok has been given a good role as BK teachers. Character education of students at SMPN 2 Depok is included in the good category, the results of the questionnaire conducted by students regarding character education with a frequency of (73.85%). This means that the character education achieved by students is in the good category. The role of teachers in character education of students at SMPN 2 Depok is in the good category. For this reason, BK teachers have given maximum roles in improving character education of students at SMPN 2 Depok. Thus, there is a role for guidance and counseling teachers in character education at SMPN 2 Depok.